2018
DOI: 10.1177/2325967118812819
|View full text |Cite
|
Sign up to set email alerts
|

Progression of the Psychological ACL-RSI Score and Return to Sport After Anterior Cruciate Ligament Reconstruction: A Prospective 2-Year Follow-up Study From the French Prospective Anterior Cruciate Ligament Reconstruction Cohort Study (FAST)

Abstract: Background:Successful return to sport after anterior cruciate ligament (ACL) reconstruction requires optimal physical and psychological recovery. The main validated tool to quantify a patient’s psychological readiness to return to sport after this surgery is the Anterior Cruciate Ligament–Return to Sport after Injury (ACL-RSI) scale.Purpose:The primary aim was to analyze the progression of the ACL-RSI score from preoperatively to 2-year follow-up. A secondary goal was to identify the factors associated with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
107
5
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(127 citation statements)
references
References 21 publications
(24 reference statements)
11
107
5
4
Order By: Relevance
“…Although there are no other studies with which to directly compare this result, it extends previous studies showing that psychological readiness is associated with return to sport. 3,16,27 More recent work also indicated that psychological readiness is associated with a second ACL injury. 20 Therefore, when combined, previous studies and this body of work emphasize the pervasive role that psychological factors play throughout the recovery period and once the athlete has returned to sport.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no other studies with which to directly compare this result, it extends previous studies showing that psychological readiness is associated with return to sport. 3,16,27 More recent work also indicated that psychological readiness is associated with a second ACL injury. 20 Therefore, when combined, previous studies and this body of work emphasize the pervasive role that psychological factors play throughout the recovery period and once the athlete has returned to sport.…”
Section: Discussionmentioning
confidence: 99%
“…8 This scale was validated by a large cohort study of 681 patients, which reported that an ACL-RSI threshold score at 6 months postoperatively was independently associated with return to preinjury sport at 2-year follow-up. 61 In 2019, a cohort study of 329 patients who returned to sport reported that patients 20 years of age or younger with a second ACL injury had lower psychological readiness scores on the ACL-RSI scale than those without second injury. 47 Early confidence may, however, be deleterious, as higher knee confidence at a younger age has been associated with a higher reinjury rate.…”
Section: Consensus Statements and Discussionmentioning
confidence: 99%
“…Hence, the two scales can be used in cross-sectional studies to determine the effect of interventions at the group level. In recent years the ACL-RSI questionnaire has increasingly been used for this purpose (Ardern, Osterberg, et al, 2014;Langford, Webster, & Feller, 2009;Muller, Kruger-Franke, Schmidt, & Rosemeyer, 2015;Sadeqi et al, 2018;Webster et al, 2008).…”
Section: Practical Implicationsmentioning
confidence: 99%